Sup-norm estimates for Bergman-projections on regulated domains - Erkkilä, Paula; Taskinen, Jari (MATHEMATICA SCANDINAVICA, 2008)
We give sufficient and necessary conditions for the boundedness of generalized Bergman projections on the space L^∞_v(Ω). The conditions depend on the geometry of the simply connected domain Ω C.